COVID-19 Surveillance and Control: Participation of All Sectors to Manage Public Health Emergency Situations in Nakhon Pathom Province - โพธิ์ศรี , ดรุณี; เอี่ยมประดิษฐ์, เอกลักษณ์; เสมาชัย, เอกพล (Journal of Health Science of Thailand, 2023)
This study is a qualitative research. The objective was to scrutinize lessons learned from emergency management service process for the control of COVID-19 with the participation of all sectors of Nakhon Pathom Province. The participants providing information were organizational leaders at the provincial level, executives, and practitioners implementing disease prevention, control, and care for COVID-19 at provincial, districts and sub-district levels. It was conducted between January 2021 – December 2022. The results showed that in Nakhon Pathom Province, there was a good surveillance and disease control system in place with participation from all sectors, The organization structure in form of incident command system was in accordance with the pattern of the Department of Disaster Prevention and Mitigation, Ministry of Interior; with some adjustment to suit the provincial context by dividing the mission into 4 important areas: administrative missions disease prevention and surveillance missions, treatment and care mission, and public relations mission. The outstanding arrangments which should be continued were the establishment of the emergency response centers at each level, the operation with participation of all sectors, and the management of morning brief meetings via video conference system to supervise and monitor daily operations. The weak points were the limited linkage of the database system of each agency and the absence of a main public health group for risk communication. Therefore, it is recommended that a risk communication group be established in the provincial public health office; production of a knowledge package on the management of surveillance, prevention and control of disease as a preparedness program toward re-emergence of COVID-19; and restructuring of the provincial communicable disease committee in order to be well prepared in the event of the emergence of severe communicable diseases.